Effect of Fiber Surface on the Interfacial Properties for Carbon Fiber Reinforced Polymer Composites. Issue 3 (March 2014) - Liu, Wenbo; Zhang, Shu; Hao, Lifeng; Zhao, Xueying; Jiao, Weicheng; Yang, Fan; Wang, Rongguo
We studied the effect of carbon-fiber surface on interfacial properties of carbon fiber reinforced plastic composites. Surface morphology and chemical composition of T-Series carbon fibers made in Japan were analyzed by scanning electron microscope and X-Ray photoelectron spectra. The wettability between carbon fibers and epoxy resin was characterized by dynamic contact angle testing. The interfacial shear strength was obtained by microbond testing, and the destruction morphology of the interface observed that was used to determine the failure mechanism.